Industrial organisation : competition, growth, and structural change - George, Kenneth Desmond; Joll, Caroline; Lynk, E. L. (London ; New York : Routledge, 1992)
As most economies remain caught in a global recession, that shows little sign of abatement, the importance of maintaining a flourishing industrial sector for the economic wellbeing of a country has rarely been so relevant. Industrial Organisation has long served as a basic introduction to this subject. The book is concerned with economic problems and policy issues that arise from the activities of firms. The authors reject the traditional micro-economic analysis of market structure in favour of studying conduct and performance in the context of macro-economic policy and the environ.
Quantitative importance of diversification Consequences for resource allocation; Chapter 5 Market structure; 5.1 INTRODUCTION; 5.2 SELLER CONCENTRATION; The measurement of concentration; The concentration ratio; The Herfindahl index; The entropy coefficient; The variance of logs; Assessment of different concentration measures; Empirical evidence on seller concentration; Determinants of concentration; Economies of scale; Sources of economies of scale; Measuring economies of scale; Changes in concentration; 5.3 OTHER DIMENSIONS OF MARKET STRUCTURE; Barriers to entry; Vertical integration
Includes bibliographical references (pages 430-443) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Industrial organization (Economic theory); Industries -- Great Britain; Industries -- European Economic Community countries; Industries -- United States; Économie industrielle; Industrie -- Grande-Bretagne.; Industrie -- Pays de l'Union européenne.; Industrie -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure; BUSINESS & ECONOMICS -- Corporate & Business History; Industrial organization (Economic theory); Industries; European Economic Community countries; Great Britain; United States; Business -- Economics